The Effectiveness of Post-Termination Health Insurance according to the Regulation of the Social Security Administration Number 5 of 2020 in Sidoarjo Regency - Resy Aprista; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to measure the effectiveness of the Social Security Agency Regulation No. 5 of 2020 and look for factors that hinder the implementation of this regulation in Sidoarjo. The research method used in this paper is sociological juridical using an empirical approach. The results of the study indicate that there is a different application from what has been regulated in the Regulation of the Social Security Agency Number 5 of 2020. This regulation is considered ineffective, because this regulation is fictitious and cannot be implemented properly. Factors that hinder the implementation of this regulation are communication factors, resource factors and also bureaucratic factors, making this regulation difficult to implement